Permian sedimentary evolution and hydrocarbon accumulation effects in the central-southern South Yellow Sea Basin - Wang, Mingjian; Huang, Long; Lei, Baohua; Zhang, Yunbo; Pan, Jun (Frontiers in Earth Science, 2023)
Abstract: Based on newly collected and processed well drilling data, cores, and seismic data of the central-southern South Yellow Sea Basin (SYSB) and adjacent areas, the understudied area, Lower Yangtze Region(LYR), is set to compare the overall sequence division and sedimentary facies explorations. The Permian contemporaneous stratigraphic framework is methodically established in the central-southern SYSB, and the corresponding sedimentary facies and their distribution are examined in some detail. Finally, together with the previous investigations of tectonic evolution, a suitable Permian accretion model is proposed. The achieved results reveal that the second-order Permian sequence developed in the central-southern SYSB is consistent with the LYR. There exists a relatively complete second-order sequence I developed in the middle-bottom section and the transgressive systems tract of sequence II in the upper section. The Permian sedimentary system in the central-southern SYSB can be compared to the Lower and is generally distributed in a northeast direction. The sequence I transgressive systems are broadly developed with the restricted platform and open platform as the dominant facies. The highstand systems tract has been only developed in the northwest of the study area, with the continental plateau as the dominant facies. The transgressive systems tract of sequence II is mostly dominated by delta facies and marsh-swamp facies with thick coal-measure layers, which provide a material basis for the formation of large-scale oil and gas fields. The thermal evolution of Permian source rocks was controlled by a combination of tectonic evolution and paleothermal gradient. Permian source rocks may have experienced secondary hydrocarbon generation in the western part of the southern depression, whereas source rocks elsewhere experience only one hydrocarbon generation in the Early Triassic. The obtained results reveal that noticeable discrepancies in the hydrocarbon accumulation patterns of various structural units could be detected.